Implementing CSR in Sharia Hotels for Sustainable Social Development: A Maqashid Sharia Perspective - Zuhroh, Ainun Amalia; Lahuri, Setiawan bin; Kozhakhmetova, Assel (Universitas Islam Sultan Agung, 2024)
This study aims to enhance the understanding of the utilization of Corporate Social Responsibility (CSR) programs in the hospitality industry of Surakarta, Central Java, Indonesia, through the lens of maqashid sharia principles. The allocation of CSR funds within the industry frequently lacks specific guidelines grounded in sharia values. To investigate this social framework, the study employs Jamaluddin Athiyyah's maqashid sharia theory, recognized for its capability to bridge classical theoretical frameworks with contemporary issues. This research adopts a qualitative approach, incorporating critical analysis and descriptive methods. Primary data were collected through interviews with representatives from Syariah Solo Hotel, Al-Multazam Hotel, and members of the community. Additionally, secondary data were gathered from the documentation of CSR programs of Islamic hotels and relevant literature, serving as empirical evidence. The findings indicate the significance of understanding Islamic teachings, particularly maqashid sharia, in the allocation of CSR funds within the hospitality sector of Surakarta. Both Islamic hotels in the region contribute to the distribution of CSR funds through religious social activities, community economic development, and educational initiatives. This aligns with the understanding of human values and the responsibilities associated with maqashid al-khalqi and maqashid ash-shari'ah as articulated by Jamaluddin Athiyyah. This study serves as a benchmark for managing maqashid sharia-based CSR funds in the hospitality industry, particularly in Indonesia. Furthermore, it provides recommendations for policymakers to supervise the use of CSR funds across various industrial sectors, ensuring alignment with religious values